Information Capacity as a Decision Factor in Information Confrontation of States - Igor F. Kefeli (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
The article is devoted to the information confrontation of states in modern conditions. The approaches of various countries to the information impact on the internal political situation of other states and measures taken at the technical and legislative level in order to counter this threat are described. The concept of «information capacity of the state» is introduced and its components are described. It is concluded that the scale of the information confrontation of states depends on factors that correlate with the components of the information capacity of the state. The use of the introduced conceptual apparatus «information capacity of the state» is a necessary condition for the success of the state policy in matters of information confrontation.